2015
DOI: 10.4034/pboci.2015.151.19
|View full text |Cite
|
Sign up to set email alerts
|

Access to and Satisfaction with Oral Health Care from the Perspective of Pediatric Cancer Patients and Their Caregivers

Abstract: Objective: To investigate the access to dental care and the oral health care provided to cancer patients aged zero to 19 years old; to detect possible difficulties hindering the delivery of oral health care; and to identify the main oral complications associated with anticancer treatment. Material and Methods: Interviews were conducted with 84 children and adolescents (or their caregivers) who were treated at Napoleão Laureano Hospital, João Pessoa County, Paraíba, Brazil; the interviews were recorded in audio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
0
6
0
1
Order By: Relevance
“…From these changes, complications in oral functions also occur and patients may become unable to feed or communicate. Moreover, oral mucositis can spread throughout the gastrointestinal tract, 8 , 9 resulting in severe discomfort that can prevent these individuals from chewing, swallowing, and speaking 10 13 …”
Section: Introductionmentioning
confidence: 99%
“…From these changes, complications in oral functions also occur and patients may become unable to feed or communicate. Moreover, oral mucositis can spread throughout the gastrointestinal tract, 8 , 9 resulting in severe discomfort that can prevent these individuals from chewing, swallowing, and speaking 10 13 …”
Section: Introductionmentioning
confidence: 99%
“…The main forms of treatment for malignant neoplasms are chemotherapy and radiotherapy, which often cause various side effects such as oral mucositis (OM) [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. This condition begins asymptomatic and, later, an erythema appears, which may be followed by erosion or ulceration of the oral mucosa, sometimes covered by a fibrinopurulent pseudomembrane and may lead to spontaneous bleeding [ 3 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…This configuration does not favor an early diagnosis of childhood cancer and contributes to an increased risk of death [25,26]. In a previous study, pediatric cancer patients from the state of Paraíba and / or their family members or caregivers reported they were provided with transportation to/from the HNL Pediatric Oncology Sector by the municipal administration [27]. Our findings indicated a higher prevalence of hematological neoplasms (66.7% of cases) in the study sample.…”
Section: Discussionmentioning
confidence: 44%
“…A study carried out in the HNL Pediatric Oncology Sector surveyed patient access to the hospital and their satisfaction with dental care services. The authors reported that most patients did not experience difficulties when seeking dental care in healthcare facilities close to their households [27].…”
Section: Discussionmentioning
confidence: 99%